Book Review : Digital Bodies: Creativity and Technology in the Arts and Humanities - Ranti Rachmawanti (Jurnal Sosioteknologi, 2023)
"Digital Bodies: Creativity and Technology in the Arts and Humanities" by Susan Broadhurst and Sara Price explores the relationship between technology and creativity in the arts and humanities. The book argues that the integration of digital technologies has had a profound impact on the way we create, produce, and consume artistic and cultural artifacts. Throughout the book, Broadhurst and Price draw on a wide range of examples from the arts and humanities, including dance, theatre, film, music, and visual art. They also engage with a range of theoretical frameworks, drawing on post-humanism, cyborg theory, and feminist theory, among others. Overall, "Digital Bodies" offers a compelling and insightful analysis of the impact of digital technologies on the arts and humanities, and the ways in which they are shaping new forms of creativity and cultural production. The book is suitable for scholars, students, and anyone interested in the intersection of technology, creativity, and culture.